Impact of microplastics on bioaccumulation of heavy metals in rape (Brassica napus L.). (February 2022) - Jia, Hao; Wu, Di; Yu, Yong; Han, Song; Sun, Long; Li, Ming
Abstract: Microplastics have become a global environmental problem due to the ubiquitous existence. The impacts of microplastics on heavy metals behaviors in aquatic environment are widely investigated, however, the impacts of microplastics on bioaccumulation of heavy metals in vegetables in terrestrial environment are seldom investigated. Herein, batch experiments were carried out, the microplastics (0.001%, 0.01%, 0.1%) and heavy metal (50, 100 mg/kg Cu 2+ or 25, 50 mg/kg Pb 2+ ) were single or combined spiked into soil to cultivate rapes ( Brassica napus L.) in greenhouse. Copper and lead contents of rapes in MP0.1+Cu100 and MP0.1+Pb50 treatments reached 38.9 mg/kg and 9.4 mg/kg, which were significantly ( p < 0.05) higher than those of Cu100 (35.3 mg/kg) and Pb50 (8.7 mg/kg) treatments, respectively. Results showed that microplastics in soil would facilitate heavy metals entering rape plants. In addition, contents of total chlorophyll, soluble sugar, vitamin C, malondialdehyde contents, activities of superoxide dismutase and guaiacol peroxidase, as well as related gene expression were analyzed to investigate the toxic effects of these pollutants (microplastics, Cu, and Pb) to rape plants. Malondialdehyde contents of rapes in MP0.1+Cu50, MP0.1+Cu100, MP0.1+Pb25, and MP0.1+Pb50 treatments reached 0.102 mmol/mg Protein, 0.123 mmol/mg Protein, 0.101 mmol/mg Protein, and 0.119 mmol/mg Protein, which were 1.42, 1.37, 1.46, and 1.45 times of those in Cu50, Cu100, Pb25, and Pb50 treatments, respectively. The changes of malondialdehyde content, activities of superoxide dismutase and guaiacol peroxidase, as well as contents of sugar and vitamin C indicated that microplastics in soil would bring severer damage and deteriorate quality of rape plants. The data in this study indicated that microplastics would increase the bioaccumulation of heavy metals in vegetables and damage to vegetables. Graphical abstract: Image 1 Highlights: Higher concentration of microplastics increased the metals accumulation of rape. Higher concentration of microplastics brought toxicity and deteriorated rape quality. Microplastics enhanced toxic effects of heavy metals to rape.